Skin antigen‐presenting cells and wound healing: New knowledge gained and challenges encountered using mouse depletion models. Issue 1 (1st March 2021) - Rajesh, Aarthi; Stuart, Gabriella; Real, Nicola; Tschirley, Allison; Ahn, Jenny; Wise, Lyn; Hibma, Merilyn
Summary: The role of antigen‐presenting cells in the skin immune system, in particular Langerhans cells and dendritic cells, has not been well defined. We recently published a study in 'Immunology' where we reported that the loss of langerin‐positive cells in the skin accelerated wound repair in the Lang‐DTR mouse. The study published here by Li, et al. reports delayed wound closure following depletion of CD11c‐positive cells in the CD11c‐DTR mouse. In this commentary, we attribute the differences between these results to several factors that differ between the studies including the depletion of different cell populations; differences in the age and the sex of mice; differences in antibiotic use between the studies; and differences in the location of the biopsies that were taken. Here, we describe the impact of these differences on wound healing and conclude that further standardization of the wound model, and further characterization of the specific cells that are depleted in these mice, is necessary to better understand how antigen‐presenting cells contribute to wound healing. Abstract : The aim of this commentary is to highlight both the importance of antigen presenting cells in wound healing, and the impact of a range of factors on results when using different antigen presenting cell depletion models.